Lymph Node Tuberculosis - Ullah, Shafi; Khan, Muhammad Aman; Khan, Ghaazaan; Rehman, Aziz ur; ., Jehanzeb; Kamal, Arshad; Begum, Norin (Journal of Postgraduate Medical Institute, 2011)
Objective:To find the frequency of tuberculosis in the lymph nodes in relationship to extrapulmonary tuberculosis and study the role of demographic factors like sex and age in the etiology of tuberculouslymphadenitis. Material and Methods:A total of 525 cases of extrapulmonary tuberculosis diagnosed in histopathologysection of The Department of Pathology, Lady Reading Hospital, Peshawar in the years 2002-2005 wereincluded in the study. Results: Out of all the extrapulmonary tuberculosis cases, 66% revealed tuberculous lymphadenitis.Seventy one percent of the patients were females in their reproductive age. Conclusion: Tuberculous lymphadenitis, after pulmonary tuberculosis, it is the second most common siteof tuberculosis, mainly affecting females in their reproductive age.